BUREAUCRATIC BEHAVIOR IN FACILITATING REGIONAL COOPERATION IN WEST KALIMANTAN PROVINCE - Siti Khotijah; Rusdiono; Pudjianto (RADJA PUBLIKA, 2025)
Regional governments are required to build cross-regional cooperation to address development challenges and increase competitiveness. The bureaucracy, as policy implementers, plays a strategic role in ensuring that regional cooperation facilitation is carried out in accordance with established regulations and objectives. This study aims to analyze bureaucratic behavior in facilitating regional cooperation with other regions in West Kalimantan Province, focusing on aspects of responsibility, responsiveness, commitment, and consistency. This study uses a qualitative descriptive approach, with data collection through interviews and observations with seven informants consisting of the Regional Cooperation Coordination Team, the Head of the Government Bureau, and representatives of technical regional apparatus. The research results show that the Government Bureau carries out its responsibility to facilitate cooperation through regulatory compliance, orderly documentation, and consistent administrative assistance. However, differences in the level of involvement between regional agencies remain a challenge that requires role harmonization. Furthermore, the responsiveness of government officials is quite good, although not all agencies are optimally utilizing communication channels. Employee commitment and consistency are also considered high, but variations in discipline and time management are still found in some work units. Overall, this research concludes that the theory of bureaucratic behavior can be applied effectively in the context of facilitating regional cooperation. The principles of responsibility, responsiveness, and commitment and consistency have proven relevant and operational in bureaucratic practice, thus serving as a normative reference for strengthening professional and sustainable regional governance. This study recommends that provincial governments strengthen coordination guidelines, digitize complaints services, evaluate performance based on bureaucratic behavior indicators, and conduct thematic training to improve the professionalism of government officials in facilitating regional cooperation.